Deregulated DNA ADP-ribosylation impairs telomere replication - Wondisford, AR; Lee, J; Lu, R; Schuller, M; Groslambert, J; Bhargava, R; Schamus-Haynes, S; Cespedes, LC; Opresko, PL; Pickett, HA; Min, J; Ahel, I; et al. (Nature Research, 2024)
The recognition that DNA can be ADP ribosylated provides an unexpected regulatory level of how ADP-ribosylation contributes to genome stability, epigenetics and immunity. Yet, it remains unknown whether DNA ADP-ribosylation (DNA-ADPr) promotes genome stability and how it is regulated. Here, we show that telomeres are subject to DNA-ADPr catalyzed by PARP1 and removed by TARG1. Mechanistically, we show that DNA-ADPr is coupled to lagging telomere DNA strand synthesis, forming at single-stranded DNA present at unligated Okazaki fragments and on the 3′ single-stranded telomere overhang. Persistent DNA-linked ADPr, due to TARG1 deficiency, eventually leads to telomere shortening. Furthermore, using the bacterial DNA ADP-ribosyl-transferase toxin to modify DNA at telomeres directly, we demonstrate that unhydrolyzed DNA-linked ADP-ribose compromises telomere replication and telomere integrity. Thus, by identifying telomeres as chromosomal targets of PARP1 and TARG1-regulated DNA-ADPr, whose deregulation compromises telomere replication and integrity, our study highlights and establishes the critical importance of controlling DNA-ADPr turnover for sustained genome stability.